Perbandingan Pengaruh Latihan Menggunakan Metode Inkuiri dengan Metode Reciprocal Terhadap Keterampilan Servis Atas dalam Permainan Bola Voli - Romadhon, Gugun Rafiq Awal Syahrul; Suhendra, Dede Iman; Rofi, Ucu Abdul (Universitas Galuh, 2022)
This study aims to compare the effect of training using the inquiry method and reciprocal method on improving upper serve skills in volleyball games. The research method used is an experiment with a true-experimental design and a two group pretest-posttest approach. The research sample consisted of 24 students of class XII SMK Ma'arif NU Banjar Patroman who were divided into two groups, each getting treatment with inquiry and reciprocal methods. The research instrument used a volleyball top serve test. The results of data analysis showed that both methods had a significant effect on improving upper serve skills. The reciprocal method provides a higher improvement (15.00%) than the inquiry method (11.67%). The t-test showed that the t-count of the inquiry method (4.10), reciprocal method (4.72), and the comparison of the two (2.09) were greater than the t-tables (1.80 and 1.72). Thus, both methods are effective, but the reciprocal method is superior in improving volleyball top serve skills.